2019
DOI: 10.3390/su11226256
|View full text |Cite
|
Sign up to set email alerts
|

Truck Scheduling Problem Considering Carbon Emissions under Truck Appointment System

Abstract: Aiming at the truck scheduling problem between the outer yard and multi-terminals, the appointment optimization model of truck is established. In this model, the queue time and the operation time of truck during the appointment period of different terminals are different. Under the restriction of given appointment quotas of each appointment period, determine the arrival amount of trucks in each appointment period. The goal is to reduce carbon emissions and total costs, improve the efficiency of truck schedulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…The major problems in the landside operations include: straddle carriers (SCs) operation optimization [36], truck appointment optimization to avoid truck congestion and reduce truck turnaround time [37], double cycling (i.e. loading and unloading simultaneously to enhance productivity) scheduling [38], route and schedule planning of rail‐mounted gantry cranes for efficient exchange of containers between the terminal and road [39], scheduling appointments of container trucks [40], and internal transport vehicle selection to avoid delays and enhance terminal performance [41].…”
Section: Marine Container Terminal and Its Key Operationsmentioning
confidence: 99%
“…The major problems in the landside operations include: straddle carriers (SCs) operation optimization [36], truck appointment optimization to avoid truck congestion and reduce truck turnaround time [37], double cycling (i.e. loading and unloading simultaneously to enhance productivity) scheduling [38], route and schedule planning of rail‐mounted gantry cranes for efficient exchange of containers between the terminal and road [39], scheduling appointments of container trucks [40], and internal transport vehicle selection to avoid delays and enhance terminal performance [41].…”
Section: Marine Container Terminal and Its Key Operationsmentioning
confidence: 99%
“…Wine [23] found that carbon emissions of automobiles changed with temperature under the same driving conditions. Fan, H et al [24] reduced carbon emissions and total transportation costs by building an optimization model for truck scheduling. Spatial and temporal measurement studies of highway carbon emissions in different countries and regions still exhibit differences, which can be attributed to variations in transportation structure, vehicle emission standards, and climate.…”
Section: Current Status Of Domestic and International Researchmentioning
confidence: 99%
“…Hoen et al [44] proposed an inventory model with carbon emission measurement methodology and considered the impact of different emission regulations. Fan et al [45] proposed a hybrid heuristic approach to assign the carbon emissions under Truck Appointment System (TAS); a realistic-sized instance of China was reported. The experimental results showed that the TAS could reduce the carbon pollution ratio by 0.22%.…”
Section: Carbon Emission Minimization In Container Transportation Problemmentioning
confidence: 99%
“…In addition, we assume that the tractor speeds with different vehicle states are all 40 km/h, and use Euclidean distance to conduct the transportation routes. The loading/unloading of one container is set one of the three options: 0.5 h, 1 h, 1.5 h. Referring to the calculation of fuel costs and carbon emissions costs in the literature [45], we set ρ 1 = 300, ρ 2 = 6.516, ρ 3 = 56.295.…”
Section: Instances Generationmentioning
confidence: 99%